A) (-5)razy(-7)+(-6)razy9-(-5)razy(-6)=
b)9razy8=(-4)razy(-7)-(-10)razy(-3)=
c) (-5)razy(-4)-(-3)razy8+(-6)razy7=
d) (-1)razy(-2)razy(-2)+(-4)razy7razy(-3)=
e) (-5)razy5razy(-2)-(-4)razy(-2)razy(-3)=
f) (-2)razy6razy(-1)+(-3)razy(-5)-(-8)razy(-4)=
g) (-3)razy(-4)+(-1)razy(-5)razy(-2)-9razy(-3)=
h)7razy6razy(-2)-(-3)razy(-1)razy(-6)+8razy(-10)-20razy(-7)=

1

Odpowiedzi

2009-11-25T19:08:35+01:00
A)(-5)...=35+(-54)-30=35-54-30=-19-30=-49
b)9*8...=72+28-30=100-30=70
c)(-5)*()-4...=20-(-24)+(-42)=20+24-42=44-42=2
d)(-1)*(-2)...=2*(-2)+(-28)*(-3)=-4+84=80
e) (-5)*5..=50-(-24)=74
f)(-2)...=12+15-32=27-32=-5
g)(-3)..=12+5*-2-(-27)=12+(-10)+27=2+27=29
h)7*6...=-84-3*-6+(-80)-(-140)=-84+18-80+140=-66-80+140=-146+140=-6